Nanoheterostructure Engineering of CdS/PbS Quantum-Dot Co-Sensitized TiO2 Nanorod Arrays for Enhanced Photoelectrochemical and Photocatalytic Properties. Issue 12 (1st January 2017) - Wang, Xingzhi; Wang, Zhuang; Zhang, Miao; Jiang, Xishun; Wang, Yanfen; Lv, Jianguo; He, Gang; Sun, Zhaoqi
Abstract : TiO2 nanorod (TNR) arrays have been sensitized by CdS, PbS, CdS/PbS, and PbS/CdS quantum-dots (QDs). The TNR arrays were synthesized by a hydrothermal treatment, and QDs were deposited on the arrays by a successive ionic layer adsorption and reaction (SILAR) technique. The morphology, structure, composition, optical, photoelectrochemical (PEC), and photocatalytic (PC) properties were systematically investigated. The results demonstrate that TNR/QDs can effectively facilitate photoinduced carrier transport, suppress the recombination rate of electron-hole pairs, and improve the visible light absorption, PEC, and PC properties. The TNR/CdS(7)/PbS(3) sample shows the maximal photocurrent density (0.91 mA/cm 2 ) and photodegradation efficiency (97.3%), which is nearly 37.9 and 2.89 times higher than those of bare TNR, respectively. The enhanced properties are attributed to the narrow band gaps and high absorption coefficients of QDs, and the type-II nanoheterostructures with a staggered alignment of band edges at the hetero-interface that can facilitate the spatial separation of electron-hole pairs.